2015
DOI: 10.1002/star.201400265
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of synthesis and characterization of oxidized starch‐graft‐poly(styrene‐butyl acrylate) latex for paper coating

Abstract: Oxidized starch-graft-poly(styrene-butyl acrylate)[OS-g-P(ST-BA)] latex with core-shell structure was synthesized by the graft copolymerization of OS with ST and n-butyl acrylate (BA) via emulsion polymerization. A three-level, four-variable Box-Behnken design was employed to investigate the effects of the concentration of OS, initiator, monomers, and temperature on the graft copolymerization. The significance of variables and their interactions were analyzed using analysis of variance and the model's signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Solid state 13 C-NMR and 1 H-NMR do not typically reveal high resolution spectra and it is recommended using cross polarized magic angle spinning (CP-MAS). The use of IR to determine grafting in an unpurified latex has limitations as homopolymer and unreacted starch will appear on the resulting spectra [88]. In-line IR analysis to track the change in starch hydroxyl or backbone hydrogens in an emulsion polymerization can yield extremely useful information relating to the rate of grafting and reaction kinetics.…”
Section: Measuring Grafting Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Solid state 13 C-NMR and 1 H-NMR do not typically reveal high resolution spectra and it is recommended using cross polarized magic angle spinning (CP-MAS). The use of IR to determine grafting in an unpurified latex has limitations as homopolymer and unreacted starch will appear on the resulting spectra [88]. In-line IR analysis to track the change in starch hydroxyl or backbone hydrogens in an emulsion polymerization can yield extremely useful information relating to the rate of grafting and reaction kinetics.…”
Section: Measuring Grafting Performancementioning
confidence: 99%
“…The precise functionalization, synthetic graft polymer formulation and final composite particle morphology all have a large effect on final film barrier properties. Starch grafted polymers exhibit a change in T g towards that of native starch, except in cases where the synthetic polymer can plasticize and disrupt the structural hydrogen bonding of the starch chains [15,88]. In some cases, the T g remains unaffected by synthetic grafts and in others (where grafting is low) two transitions are observed (synthetic polymer and starch).…”
Section: Film Propertiesmentioning
confidence: 99%
“…Potassium or ammonium persulfate initiation was also used to graft others polymers for specific applications (Table ) .…”
Section: Grafting From Via Radical Polymerizationmentioning
confidence: 99%
“…According to a study reported by [79], bioethanol extracted from Sri Kanji 1 cassava starch is way much cheaper as compared to gasoline fuel. Starch also helps in enhancing paper coating industry [80,81]. Thus, starch is necessary for food, pharmaceutical, edible film, bioethanol products and paper coating industry.…”
Section: Application Of Starchmentioning
confidence: 99%